Concentration of Selected Elements and Antioxidative Potential in a Group of Males Working in the Metal Industry: Elements And Antioxidative Potential In Men. Issue 3 (20th May 2019) - Charkiewicz, Angelika Edyta; Omeljaniuk, Wioleta Justyna; Orywal, Karolina; Czygier, Małgorzata; Szmitkowski, Maciej; Mroczko, Barbara; Maślach, Dominik; Szpak, Andrzej
The purpose of this study was to show that some elements have a proven antioxidative effect and are essential for the proper development and functioning of the human body. The study also assessed the concentration of selected elements and total antioxidant status (TAS) in a group of male inhabitants of Białystok, Poland, who are professionally active in the metal industry. The study group comprised 163 men aged 55–64 years. The concentration of the analyzed elements was determined using flame (Zn and Cu) and electrothermal (Se, Cd, and Pb) atomic absorption spectrometry. Spectrophotometric test kits were used to assay the TAS and glutathione reductase (GR) activity in serum. The results suggested the mean concentration of Se in serum was 54.04 ± 12.10 μg/L, which was below the reference range. A significant negative correlation was observed between the concentration of Se in the serum and Pb and Cd concentrations in the whole blood of the studied men. The concentrations of the other elements, antioxidant potential, and GR activity were within the reference range. A statistically significant positive correlation was observed between Pb and Cd, indicating combined exposure and a considerable negative correlation between lead and selenium as well as between lead and TAS. Selenium and TAS are likely to modify the adverse effects of Pb in the bodies of the studied men. The results indicate that it is necessary to constantly monitor men who are occupationally exposed to heavy metals, maintain a healthy lifestyle, and introduce effective preventive measures at a local level.